Ultrasound imaging for measuring muscle and subcutaneous fat tissue thickness of the anterior thigh: a 2 year longitudinal study in middle age. Issue 1 (14th January 2020) - Mechelli, Filippo; Arendt‐Nielsen, Lars; Stokes, Maria; Agyapong‐Badu, Sandra
Abstract: Background: Ultrasound (US) imaging technique is widely used in research and clinical settings to assess the morphology and morphometry of neuromusculoskeletal structures. The technique has reported validity and reliability in measuring the size of various muscles under controlled conditions. The aim of the present study was to assess anterior thigh thickness using US imaging, in a healthy cohort of middle‐aged older adults. Methods: Participants included 17 healthy older adults involved in regular moderate‐vigorous activities (age range 39–66 years). US imaging scans of the anterior thighs 2 years since baseline measurements were performed. Images were analysed offline to compare US imaging measurements of muscle thickness and subcutaneous fat (SF) of the anterior thigh taken at baseline and after 2 years. Results: There was no significant difference between muscle thickness measurements taken at baseline and after 2 years (mean, standard deviation; baseline = 2.80 ± 0.71 cm; follow‐up = 2.77 ± 0.72 cm, P  = 0.33). There was also no significant change in SF thickness (baseline = 1.04 ± 0.41 cm; follow‐up = 1.06 ± 0.40, P  = 0.33). Conclusions: The results show that there was no decline in anterior thigh muscle thickness or increase in SF in the healthy cohort studied using US imaging over a 2 year period. These findings demonstrate the robustness of US imaging measurements over time.